Seismic Wave‐Based Constraints on Geodynamical Processes: An Application to Partial Melting Beneath the Réunion Island. (8th May 2020) - Franken, T.; Armitage, J. J.; Fuji, N.; Fournier, A.
Abstract: The inversion of seismic observations leads to maps of the interior of the Earth that can be interpreted. Regions of low seismic velocity have historically been interpreted to be due to factors related to high‐temperature and high‐melt retention. Subsequently, geodynamic models can be used to test such interpretations. However, the inversions are nonunique, and arguably, it would be best to test geodynamic scenarios against observations rather than interpretations. Here we make a first attempt at this. At depths greater than 80 km below Réunion, a low shear‐wave velocity zone is imaged. Rather than interpret this inverted model, we test a forward model of melt generation and retention against seismic observations. Geodynamic model solutions are converted with a mineral parameter database to P wave and S wave velocity profiles from various initial temperatures T, upwelling velocities v ‾, and permeabilities k 0 . By embedding these velocity profiles, synthetic seismograms are generated. For a range of k 0, T, and v ‾, we generate synthetic traces for 21 teleseismic events registered at a receiver on Réunion island. We measure the traveltime difference between observed and synthetic waveforms and the interphase differential travel times for 210 scenarios for several phase arrivals of three components, filtered between 0.01 and 0.2 Hz. The results indicate that upper mantle temperatures beneath Réunion lie within 1400–1450 °C, with permeability coefficients of 10 −5 –10 −6 m 2 . These conditions are associated with porosities of <0.28% and high‐melt extraction rates of 8.37–18.35 m·year −1 . This study demonstrates the potential for fully comparing geodynamic scenarios with seismic observations. Key Points: We combine geodynamic modeling with seismic wave propagation to constrain the state of the dynamics underneath the Réunion island We analyze the sensitivity of seismic observables to geodynamical parameters Our results favor high‐melt extraction rates underneath the Réunion island